ANALYSIS OF CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING FINANCING (NPF) AND FINANCING TO DESPOSITO RATIO (FDR) TO PROFITABILITY RETURN ON ASSET (ROA) AT BNI SYARIAH BANK FOR THE 2011-2020 PERIOD - Budiastuti Fatkar; Riska Alicia; Umi Kulsum; Srie Nuning Mulatsih; Hery Erdi (Jurnal Scientia, 2023)
This research was conducted on a banking company in Indonesia, Bank BNI Syariah with the aim of determining the influence between Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) and Financing to Desposito Ratio (FDR) on Profitability Return On Asset (ROA). Researchers use quantitative data in the form of secondary data obtained from data from the Financial Statements of Bank BNI Syariah for the 2011-2020 period. The research method carried out is to use the Causal Associative method. The analyst technique used in this study is multiple regression analysis to test the effect of Capital Adeqacy Ratio (CAR), Non Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on Return On Asset (ROA). While the classical assumption test used in this study includes normality test, autocorrelation test, multicollinearity test, heterochedasticity test. Test the hypothesis simultaneous influence test (F test) and partial influence test (t test). The results of this study state that